Pathways of healthcare and antibiotics use following reported gastrointestinal illness: a cross-sectional study in rural Anhui, China. Issue 8 (20th August 2019) - Shen, Xing Rong; Xie, Maomao; Chai, Jing; Feng, Rui; Cheng, Jing; Liu, Rong; Kadetz, Paul; Wang, DeBin
Abstract : Objective: To document the factors, and their pathways, that influence healthcare and antibiotics use following reported gastrointestinal illnesses in Anhui province, China. Study design: This study uses cross-sectional design, descriptive statistical analysis, pathway mapping and multivariate logistic regression modelling. Setting: Households in 12 villages in Anhui province, China. Participants: A total of 3659 residents who: (1) held a registered rural residence and were actually living in the sampled villages when this study was conducted; (2) were aged 18 years and older and (3) were willing to participate and able to answer the survey questions. Outcome measures: Planned and measured variables included the occurrence of gastrointestinal illness, professional care seeking and antibiotic use due to the illness and factors influencing these measures. Results: Of the 3659 informants, 29.0% reported gastrointestinal illness episodes in the past year. Of these episodes, 50.2% led to professional care seeking and 65.4% of antibiotic use. Multivariate logistic modelling identifies that: (1) reported gastrointestinal illnesses were more frequent in north compared with middle (OR 0.569, 95% CI 0.472 to 0.686) and south (OR 0.588, 95% CI 0.492 to 0.702) Anhui, and were positively associated with age (B=0.123, p<0.05), knowledge concerning (B=0.248, p<0.05) and practice of (B=0.184, p<0.05) prevention; (2) seeking professional care and antibiotic use following the illness was linked to the severity of symptoms and geographical locations, rather than to specific pathogenic features. Conclusions: Reported gastrointestinal illnesses are quite prevalent in the sample population and a large proportion of these have resulted in professional care and antibiotics use. The factors associated with the reported illnesses and pathways of healthcare and antibiotic use, as identified in this study, should inform future research and intervention efforts.